2014
DOI: 10.1021/am500812h
|View full text |Cite
|
Sign up to set email alerts
|

Polyamidoamine Dendrimer and Oleic Acid-Functionalized Graphene as Biocompatible and Efficient Gene Delivery Vectors

Abstract: Functionalized graphene has good potential in biomedical applications. To address a better and multiplex design of graphene-based gene vectors, the graphene-oleate-polyamidoamine (PAMAM) dendrimer hybrids were synthesized by the oleic acid adsorption and covalent linkage of PAMAM dendrimers. The micromorphology, electrical charge property, and amount of free amine groups of the graphene-oleate-PAMAM hybrids were characterized, and the peripheral functional groups were identified. The PAMAM dendrimers could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 72 publications
(130 reference statements)
0
66
0
Order By: Relevance
“…In order to increase the cellular uptake of GBM nanoplatforms, membrane penetrating peptides or acids were added via various approaches. As an example, oleic acid, which exhibits a high affinity with the cell membrane and promotes its destabilization, was used to functionalize graphene and GO in combination with PAMAM dendrimers 61 . Additionally, the cationic cell penetrating peptide octaarginine was covalently engrafted onto GO flakes 63 doxorubicin onto GO-PEI-PEG using a MMP2-cleavable peptide linkage, consequently allowing the release of doxorubicin only in the presence of the enzyme, which is over expressed in cancer cells 41 .…”
Section: Strategies To Optimize Gbms As Gene Delivery Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the cellular uptake of GBM nanoplatforms, membrane penetrating peptides or acids were added via various approaches. As an example, oleic acid, which exhibits a high affinity with the cell membrane and promotes its destabilization, was used to functionalize graphene and GO in combination with PAMAM dendrimers 61 . Additionally, the cationic cell penetrating peptide octaarginine was covalently engrafted onto GO flakes 63 doxorubicin onto GO-PEI-PEG using a MMP2-cleavable peptide linkage, consequently allowing the release of doxorubicin only in the presence of the enzyme, which is over expressed in cancer cells 41 .…”
Section: Strategies To Optimize Gbms As Gene Delivery Platformmentioning
confidence: 99%
“…Most of such studies do not surpass the proof-of-principle stage, assessing transgene expression but without therapeutic goals. They have explored a variety of functionalization strategies 37,45,46,52,56,64 , the conjugation to molecules that facilitate cell and nuclear internalization 42,61,63 as well as the combination with other nanoparticles 43 , all already discussed in the previous section, in an attempt to increase the efficiency of gene transfer. However, it is difficult to establish direct comparisons between the results achieved by these studies given the numerous factors Ģ¶ e.g.…”
Section: Intracellular Molecular Sensingmentioning
confidence: 99%
“…Graphene and its analog, TMDCs, which are the two-dimensional (2D) sp 2 -bonded nanocarbon with excellent electronic, optical, and mechanical properties have been extensively studied in the past decades [31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…Liu et al developed a PAMAM and oleic acid functionalized GO nanocomposite and demonstrated transfection of HeLa and MG63ĀÆbroblast cells with luciferase gene at a high transfection eĀ±ciency. 67 These composites also showed good physiological stability.…”
Section: Graphene-based Nanomaterials For Nucleic Acid Deliverymentioning
confidence: 95%